Revitalizing the School Literacy Movement: Strategies for Strengthening Literacy Culture in Senior High Schools of Bangka Belitung Islands - Taufiq, M. Aries; Herza, Herza; Pangestu, Fajar Agung; Harianto, Harianto; Fa, Jong Li; Manalu, Herland Franley (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2025)
The School Literacy Movement (Gerakan Literasi Sekolah/GLS), launched nationally in 2015, aims to cultivate a reading and writing culture among Indonesian students. In the post-pandemic era, however, its implementation faces new challenges and calls for revitalization. This qualitative descriptive study explored the implementation of GLS in senior high schools in the Bangka Belitung Islands, focusing on (a) current practices and challenges, (b) the roles of principals, teachers, and students, and (c) strategies for strengthening literacy culture. Data were collected from 8 senior high schools through semi-structured interviews with 42 participants (principals, teachers, and students) and classroom and school environment observations. Then, the data were analyzed using a thematic analysis approach. Findings showed that while schools continued routine activities, such as the 15-minute reading program and the creation of reading corners, challenges persisted, including limited resources, uneven stakeholder engagement, and barriers specific to archipelagic contexts. Some schools, however, displayed strong leadership and community participation. To revitalize GLS, this study recommends integrating digital and print literacy resources, enhancing teacher capacity, promoting student-centered projects, and fostering collaboration with families and local communities. Unlike previous studies that primarily focused on policy-level implementation, this study provides contextual insights into literacy practices in an archipelagic region, highlighting the importance of geographically responsive strategies for literacy development. These findings underscore the need for contextualized, sustainable approaches to literacy development and provide guidance for policymakers, educators, and stakeholders in advancing literacy culture in Indonesia’s post-pandemic education landscape.